Management of Hazardous and Toxic Waste (B3) at Puskesmas in Jember District - Khoiron, Khoiron; Anggita I.F, Puteri (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
Puskesmas X serves various programs such as health check-ups, outpatient care, inpatient care, emergency room services, and so on. The purpose of this research is to determine the type of B3 waste, the amount of B3 waste heap, the B3 waste treatment system, and also the impact that will be caused by poor B3 waste management. The type of study in this research is descriptive observational. This activity was carried out on February 14 to March 31, 2022. The data sources in this study were obtained from 4 (four) ways, namely by observation, interviews, weighing and documentation. The results of this study indicate that the types of waste (B3) in Puskesmas X are used syringes, expired syringes, expired drugs, soft infectious waste (used gloves, cotton, bandages, tissue, masks, used drug packaging, and used injection packaging), and infusion bottles. Sources of B3 waste come from service units such as the emergency room, immunization room, general treatment room, inpatient room, MCH room, laboratory room, delivery room, and dental and oral service room. The largest solid medical waste producer at Puskesmas X was from the delivery room unit with an average daily weight of 0.458 Kg and the laboratory room with an average daily weight of 0.299 Kg. B3 waste management in Puskesmas X is by collaborating with PT Sagraha Satya Sawahita and PT. International Wastec. Poor management of medical waste can lead to health hazards such as infection, hepatitis, HIV and Aids, respiratory or skin diseases, cancer, damage to offspring, and death.